Bound Water in Starch Hydrogels with High Dispersed Silica - Turov, V. V.; Novza, A. A.; Leboda, R.; Skubisewska-Zieba, J.; Szesniak, M.; Turov, K. V. (Problems of Cryobiology and Cryomedicine, 2005)
Gel-like colloid starch solutions and the effect of high dispersed silica on their phase state were studied using the method ofliquid phase layered freezing-out with 1H NMR recording of unfrozen water signal. Interphase energy of â€œbiopolymer-waterâ€ system was established to increase from 65 to 194 J/g during starch gel dilution. Silica greatly affects the phase state of starch gel. Secondary structure of amylopectin chains is disintegrated in its presence and the stable â€œstarch-silicaâ€ complexes are formed. Concentration of bound water in such complexes is lower than in starch gels and greatly depends on starch-silica concentration ratio. Interphasewater energy in â€œstarch-water-silicaâ€ systems makes 21-103 J/g.